Editorial Perspective: Perils and promise for child and adolescent sleep and associated psychopathology during the COVID‐19 pandemic - Becker, Stephen P. (J Child Psychol Psychiatry, 2020)
It is anticipated that the novel coronavirus disease 2019 (COVID‐19) pandemic and associated societal response will have wide‐ranging impacts on youth development and mental health. Sleep is crucial for child and adolescent health and well‐being, and the potential for sleep problems to emerge or worsen during and following the pandemic is high. This may be particularly true for children and adolescents who are at heightened risk for the onset of sleep and mental health disturbances and for those whom developmental changes impacting sleep are rapidly occurring. Youth with preexisting psychopathologies (including anxiety and depression) and neurodevelopmental conditions (including attention‐deficit/hyperactivity disorder and autism spectrum disorder) could be especially vulnerable to disturbed sleep during this period of change and uncertainty. It is thus imperative that sleep considerations be part of research and clinical initiatives aimed at understanding and mitigating the impact of the COVID‐19 pandemic in children and adolescents. This article considers ways in which the pandemic may impact sleep, including research and clinical implications.